Development of Value Added Agricultural Community Product Learning Packages Using Mixed Method Research Approach - Wangkaewhiran , Thipwimol; Meekhobtong, Sirinthorn; Panyapisit, Jittima; Kosila, Jiratchaya; Siripallop, Thanathep; Wongnarat, Apiwat; Soontornsanee, Jarruwan (Journal of Applied Economics and Management Strategy, 2024)
The objectives of this research were 1) to study the results of using a participatory action research to synthesize agricultural product learning packages in the community of farmers in Chachoengsao Province, 2) to create value added learning packages of agricultural products in Chachoengsao Province community, and 3) to study guidelines to create innovations for enhancing the competitiveness of agribusiness from community products for sustainable self-reliance of Chachoengsao Province. The target groups in the research were farmers, local people intellectuals, agricultural expert in rice production and processing representatives from relevant government agencies in Chachoengsao Province. The data were analyzed by 1) basic statistics such as percentage, mean (x̅), standard deviation (S.D.), and 2) content analysis for qualitative analysis. The research results were as follows: 1. The results of using a participatory process to synthesize agricultural product learning packages in the community of farmers found that farmers needed a knowledge set to create added value to expand products from "rice" to "rice flour" to be processed into community products in Chachoengsao Province, and the use of agricultural products in the herbal group for processing which led to food preservation to reduce household expenses. 2. The learning packages on creating value added of agricultural products in the Chachoengsao Province community consisting of 3 product groups: (1) bakery product, including Soft Riceberry Cookies with Mango Jam and Organic Rice Cookies (2) food product and food preservation, including Herbal Chili Paste and Organic Rice Meatballs, and (3) bath and skin care products, including Riceberry Milk Shower Cream. The results of the evaluation of the acceptance in overall average in acceptance was at a high level (x̅ = 4.40) 3. The guidelines to create innovations for enhancing the community agricultural products businesses competitiveness for self-reliance sustainability by adding product strengths into business value (Value Propositions). The local wisdom combined together with local community identity, in addition with the production process begin with selection of quality local ingredients, chemical free cultivation, should be delivered to consumers, as well as presenting stories (Story telling) by local people and under three distribution channels: (1) retail and wholesale at the storefronts, (2) out bound flea market and 3) call and online ordering channels. There should be regular product advertising at the points of sale.